Uma análise das pautas de exportação brasileira e indiana para os Estados Unidos - Bertozo, Laís Di Giovanni (2011)
This work estimates the similarity and variety indexes to evaluate the competition of Indian products on Brazilian products in the U.S. from 2001 to 2009. The main results were that the similarity between the goods of Indian and Brazilian exports is relatively low and do not follow a trend and that the variety of Indian products in the U.S. market is well above the Brazilian products.